(untitled) (World Bulletin of Public Health, 2023)
In the last years the growth of autoimmune diseases with systemic lupus erythematosus takes a special place; possibilities of modern diagnostics, population awareness, factors of environmental disadvantage (Priaralie), consequences of COVID 19 have become the reflection on the character of the disease and its complications.